Well differentiated arginase-1 negative hepatocellular carcinoma - Obiorah, Ifeyinwa E. (Transl Gastroenterol Hepatol, 2019)
BACKGROUND: The diagnosis of hepatocellular carcinoma (HCC) is dependent on the histologic and immunohistochemical analysis of biopsy and resection specimens. The distinction of HCC from metastatic neoplasms is pertinent for treatment and prognostic purposes. Arginase-1 (Arg-1), a marker of hepatocellular differentiation, has shown superior sensitivity and specificity when compared to other immunohistochemical markers of detection of HCC such as hepatocyte paraffin antigen (HepPar-1). Studies have shown that poorly differentiated HCC can lose arginase expression, however well differentiated HCC are rarely ever arginase negative. METHODS: In this study Arg-1 expression was detected using immunohistochemical staining on tissue specimens from 40 confirmed cases of well differentiated HCC specimens using a highly specific monoclonal antibody for Arg-1. Specificity of the Arg-1 antibody was evaluated by immunostaining of 24 non-HCC tumors in the liver and 200 non-liver neoplasms using paraffin block and tissue micro-array (TMA) based immunohistochemistry. RESULTS: Four well differentiated HCC cases were found to be completely negative for Arg-1 and similarly all 224 non-HCC tumors did not express Arg-1. The arginase negative well differentiated tumors were positive for other hepatocellular markers such as HepPar-1 and polyclonal carcinoembryonic antigen (pCEA). Of the four tumors, only one recurred at 28 months. All patients are currently stable with a mean survival of 43 months. CONCLUSIONS: Arg-1 negative well differentiated HCC can be a clinical dilemma which can lead to misdiagnosis. Confirmation with other hepatocellular markers such as HepPar1 and pCEA is essential in making the correct diagnosis. The clinicopathologic outcomes of arginase negative well differentiated HCC has been poorly characterized, thus our findings are of utmost importance in understanding the clinical behavior of these tumors. This may have a potential role in understanding the mechanism of the use of targeted therapy in HCC tumors.